DAMPAK EKONOMI DESA MELALUI WISATA PANTAI WANE DALAM PERSPEKTIF EKONOMI ISLAM KEC. MONTA, KAB. BIMA - nur wati nurwati (Nurul Jadid University, 2023)
This study aims to determine the economic impact of villages through wane beach tourism in the Islamic Economic Perspective of Monta District, Bima District. Research using desk research methods with online data and information search techniques, secondary sources, and scientific publication sources. While the analytical techniques used are qualitative descriptive analysis techniques, analogies, comparisons of several research results and other scientific publications with the problems of the economic dimension of the village through tourist beaches. The results showed that there are two aspects in the village economy, the first is the positive aspect for the village economy, increasing village economic income, Making villages more exposed, transportation roads are asphalted, household economies increase, fishermen have the opportunity to sell fish. The Islamic economic view of the impact of tourism villages focuses on welfare, justice, and utilizing the environment without damaging the environment. While the negative aspects for the village economy are the lack of village security, high crime rates on visitors that hinder local tourists from visiting and will reduce village income. In view of economics Islam is to strongly condemn the acts that are zhalim and the level of crime that results in harm to others.